Plan de seguridad informática basado en la norma Iso 27002 para mejorar la gestión tecnológica del colegio carmelitas – Trujillo - Cortéz Rodríguez, Amelia Ivon (2018)
The present research work entitled “Plan de Seguridad Informática basado en la Norma ISO 27002 para mejorar la Gestión Tecnológica del Colegio Carmelitas – Trujillo”, has been made with the purpose of improving the technological management in the aspects of computer security (hardware, software, operations and services), which in turn is part of information security. Among the specific objectives set for this thesis was: securely manage all the assets of the institution, control access to the institution's computing resources, define encryption policies, establish physical and environmental security throughout the institution, establish security in business operations, establish security in telecommunications and define adequate measures for the acquisition, development and maintenance of information systems. The design of the research has been Non-Experimental, Transversal because the data collection will be done in a single moment. The design of the research design was simple descriptive. The methodology used for the development of this thesis is based on the use of security controls at the operational level of the international standard ISO 27002: 2013, which correspond to a computer security plan itself. The selected security controls were: asset management, access control, encryption, physical and environmental security, security in operations, security in telecommunications and acquisition, development and maintenance of information systems. As for the achievements, these are reflected in the conclusions of this thesis, where each of them allows to observe, measure and quantify the fulfillment of the objectives set at the beginning of the present investigation.